Analisis Smat Rubbishbin Untuk Rumah Kos Berbasis IOT - Marli Yansyah; Tata Sutabri (Journal of Creative Student Research, 2024)
Trash cans play a very important role in homestead equipment. Some boarding houses employ staff to dispose of children's rubbish and have installed rubbish disposal systems. In this case, the Internet of Things (IoT) technology system can be used to develop trash bins to make people's tasks easier in their daily lives. Based on this problem, the capacity of trash cans has been increased so that employees can more easily control the contents of children's trash cans in Islamic boarding schools by creating IoT technology with a system that can provide information about the contents of trash cans. We use a monitoring system on our website. In addition, smart trash cans are equipped with humidity sensors to detect whether wet waste needs to be thrown away immediately.